Penerapan Undang-Undang Perlindungan Anak dalam Mengamankan Data Pribadi Anak yang Berkonflik dengan Hukum di Era Digital - Faloygama, Gordianus Pradino; Cahyo, Cahyo (HUMANIORUM, 2025)
The protection of children's personal data in cyberspace has become an increasingly important issue with the rapid advancement of digital technology. In Indonesia, the Child Protection Law (UUPA) aims to provide protection for children, including their personal data. However, the effectiveness of implementing this law to safeguard children’s personal data in conflicts with the law in the digital era faces various challenges. The first research question examines the effectiveness of the implementation of UUPA in protecting children's personal data, while the second question addresses focused on how to protect children personal data based on implementation of the law. The discussion reveals that the main challenges include a lack of understanding about the importance of protecting children's personal data, digital literacy disparities, weak supervision of digital platforms, and limited enforcement of cybercrimes. Moreover, cross-border legal issues and the lack of readiness of law enforcement officials in handling cybercrimes involving children exacerbate the protection of children's personal data. The recommendations include enhancing digital literacy, strengthening regulations, and fostering collaboration between the government, private sector, and society to create a safer online environment for children.